ANALISIS PELAKSANAAN DI BIDANG PELAYANAN BPJS YANG FOKUS PADA ADMINISTRASI KEPERSERTAAN DAN PROSES KLAIM JAMINAN SOSIAL - Nadila Nadila; Ita Mustika; Maya Richmayati (PUAN INDONESIA, 2026)
Field Work Practice (KKL) is an integral part of the academic curriculum designed to bridge the gap between theoretical knowledge and practical application. This study aims to analyze the implementation of public service delivery at the Social Security Administration Agency for Employment (BPJS Ketenagakerjaan) in Nagoya Batam Branch, with a specific focus on participant administration and social security claims processes. A qualitative descriptive method was employed, utilizing direct observation, active participation in operational activities, and documentation throughout the internship period. The findings reveal that BPJS Ketenagakerjaan has established a service system characterized by responsiveness, accuracy, and technological integration. Despite the progress, several operational challenges remain, including unstable internet connectivity and limited hardware capacity. This practical experience has provided students with firsthand insight into public administration processes, service quality management, and the application of digital tools in social security services. The study underscores the importance of experiential learning in strengthening students’ professional competencies and preparing them for the dynamics of the public sector workforce.